TGF-β signaling links E-cadherin loss to suppression of nucleotide excision repair - Qiang, Lei (Oncogene, 2015)
E-cadherin is a cell adhesion molecule best known for its function in suppressing tumor progression and metastasis. Here we show that E-cadherin promotes nucleotide excision repair through positively regulating the expression of xeroderma pigmentosum complementation group C (XPC) and DNA damage-binding protein 1 (DDB1). Loss of E-cadherin activates the E2F4 and p130/107 transcription repressor complexes to suppress the transcription of both XPC and DDB1 through activating the TGF-β pathway. Adding XPC or DDB1, or inhibiting the TGF-β pathway, increases the repair of UV-induced DNA damage in E-cadherin-inhibited cells. In mouse skin and skin tumors UVB radiation down-regulates E-cadherin. In sun-associated premalignant and malignant skin neoplasia, E-cadherin is down-regulated in association with reduced XPC and DDB1 levels. These findings demonstrate a crucial role of E-cadherin in efficient DNA repair of UV-induced DNA damage, identify a new link between epithelial adhesion and DNA repair, and suggest a mechanistic link of early E-cadherin loss in tumor initiation.